Art Nail Polish and Henna as Inclusive Art Learning Media for Students with Special Needs in Special Schools - Wirma Surya (LPPM Institut Seni Indonesia Padangpanjang, 2025)
Art education for students with special needs in Special Schools requires adaptive, contextual, and inclusive learning media that accommodate diverse abilities and learning characteristics. This study aims to examine the use of art nail polish and henna as inclusive art learning media that support the development of creativity, fine motor skills, and self-expression among students with special needs. The research employed a qualitative approach using a case study design, involving Special School students as research participants through applied art practice activities. Data were collected through participatory observation, documentation of learning processes and student artworks, and in-depth interviews with accompanying teachers. The findings indicate that the use of art nail polish and henna increases students’ active engagement in the learning process, enhances fine motor coordination, and encourages confidence in expressing visual ideas independently. In addition, these media effectively create a joyful and inclusive learning environment, thereby minimizing psychological and social barriers in art learning. This study offers an alternative body-based applied art medium that remains underexplored in formal special education contexts. The conclusion emphasizes that art nail polish and henna can serve as alternative inclusive art learning media in Special Schools, provided that intensive guidance, safe material selection, and methodological adjustments aligned with students’ individual needs are implemented